Implementasi Sistem Informasi UPTD Pengembangan Sentra Keramik Plered Berbasis Web - Sibarani, Mentiana; Sipayung, Evasaria Magdalena; Supratman, Deny (Jurnal Telematika, 2019)
The Regional Technical Implementation Unit (UPTD) for the Development of the Plered Ceramics Center in Purwakarta became one of the centers of research and development of pottery and ceramics. In addition to be an educational tour for a number of local and outside students of Purwakarta Regency, UPTD Ceramics Plered located in Purwakarta is used as a source of knowledge development for ceramic craftsmen from outside the city. The activities in UPTD Ceramics Plered are in the form of training and events, training is given by UPTD to the community to be able to take part in the training held by UPTD Ceramics Plered and events for craftsmen so they can participate in the event. Information on activities and products can be obtained from a web-based information system. Development of UPTD information systems Development of web-based Ceramic Plered Centers using PHP with Laravel Framework, databases using MySQL. The information system that has been developed has been implemented with the url http://uptdkeramik.purwakartakab.go.id. The information obtained consisted of information about UPTD Plered, products in the form of pottery and ceramics, activities and news. Activity data consists of event containing event data to be carried out and can be followed by artisans and training containing activity data to be carried out by UPTD Plered which can be followed by registering the training.Unit Pelaksana Teknis Daerah (UPTD) Pengembangan Sentra Keramik Plered di Purwakarta menjadi salah satu pusat penelitian dan pengembangan gerabah dan keramik. Selain menjadi wisata edukasi bagi sejumlah pelajar lokal maupun luar Kabupaten Purwakarta, UPTD Pengembangan Sentra Keramik Plered yang berada di Purwakarta ini dijadikan sebagai sumber pengembangan ilmu bagi pengrajin keramik dari luar kota. Kegiatan yang ada di UPTD Pengembangan Sentra Keramik Plered berupa pelatihan dan event. Pelatihan yang diadakan oleh UPTD Pengembangan Sentra Keramik Plered diberikan untuk dapat diikuti masyarakat dan event kepada pengrajin sehingga dapat mengikuti event tersebut. Informasi kegiatan maupunproduk bisa didapatkan dari sistem informasi berbasis web. Pengembangan sistem informasi UPTD Pengembangan Sentra Keramik Plered berbasis web menggunakan PHP dengan Laravel Framework dan database menggunakan MySQL. Sistem informasi yang telah dikembangkan ini sudah diimplementasikan dengan URL http://uptdkeramik.purwakartakab.go.id. Informasi yang diperoleh terdiri dari informasi tentang UPTD Plered, produk berupa gerabah dan keramik, kegiatan dan berita. Data kegiatan terdiri atas event yang berisi data event yang akan dilaksanakan dan diikuti oleh pengrajin dan data pelatihan yang berisi data kegiatan yang akan dilakukan UPTD Plered yang diikuti dengan cara mendaftar pelatihan tersebut.